King Richard II - Edited by Gurr, Andrew (Cambridge, New York Cambridge University Press, 2012)
Hakespeare knew like few others how to dramatize the gossipy lives of kings. More importantly, he knew that just because it was history, that didn't mean it was boring. Today, however, Shakespeare's histories can be a bit of a drudge to plow through. Let BookCaps help with this modern translation of the classic history play.
Keywords: Richard II, King of England, 1367-1400 -- Great Britain